If we have a logarithmic expression \[\log x:\log y:\log z = (y - z):(z - x):(x - y)\] then which of the following expressions is true?
A). \[{x^x}.{y^y}.{z^z} = 1\]
B). \[{x^y}.{y^z}.{z^x} = 1\]
C). \[\sqrt[x]{x}\sqrt[y]{y}\sqrt[z]{z} = 1\]
D). None of these
Answer
Verified
482.1k+ views
Hint: This is a typical logarithmic property question. We will need to use the property \[x\log x = \log \left( {{x^x}} \right)\] to get the final answer. Also we will need some properties of ratio to get started.
Complete step-by-step answer:
It is given that \[\log x:\log y:\log z = (y - z):(z - x):(x - y)\]
Then we can let that,
\[\dfrac{{\log x}}{{y - z}} = \dfrac{{\log y}}{{z - x}} = \dfrac{{\log z}}{{y - z}} = k\]
So from here we can get
\[\begin{array}{l}
\log x = k(y - z)...................................(i)\\
\log y = k(z - x)................................(ii)\\
\log z = k(x - y).................................(iii)
\end{array}\]
Now if we multiply equation (i) with x, equation (ii) with y and equation(iii) with z
We will get its as
\[\begin{array}{l}
x\log x = kx(y - z)\\
y\log y = ky(z - x)\\
z\log z = kz(x - y)
\end{array}\]
So now let us add all three of them and we will get it as
\[\begin{array}{l}
\therefore x\log x + y\log y + z\log z = kx(y - z) + ky(z - x) + kz(x - y)\\
\Rightarrow x\log x + y\log y + z\log z = k\left( {xy - xz + yz - xy + yz + xz - yz} \right)\\
\Rightarrow x\log x + y\log y + z\log z = k \times 0\\
\Rightarrow x\log x + y\log y + z\log z = 0
\end{array}\]
Now by using the property of log, \[x\log x = \log \left( {{x^x}} \right)\] we will get the whole thing as
\[ \Rightarrow \log \left( {{x^x}} \right) + \log \left( {{y^y}} \right) + \log \left( {{z^z}} \right) = 0\]
Now again we know that \[\log x + \log y + \log z = \log (xyz)\]
So by using this property of log we are getting
\[ \Rightarrow \log \left( {{x^x}.{y^y}.{z^z}} \right) = 0\]
Again if we take the log to the other side we will get it as
\[ \Rightarrow \left( {{x^x}.{y^y}.{z^z}} \right) = 1\]
Which is the correct answer and which means that option A is the correct option here.
Note: \[\log x = 0\] is \[x = 1\] because we know that logarithm in mathematics is treated as log base e so here \[{\log _e}x = 0\] is basically \[x = {e^0} = 1\] . In other words we can also say that the antilog of 0 is 1.
Complete step-by-step answer:
It is given that \[\log x:\log y:\log z = (y - z):(z - x):(x - y)\]
Then we can let that,
\[\dfrac{{\log x}}{{y - z}} = \dfrac{{\log y}}{{z - x}} = \dfrac{{\log z}}{{y - z}} = k\]
So from here we can get
\[\begin{array}{l}
\log x = k(y - z)...................................(i)\\
\log y = k(z - x)................................(ii)\\
\log z = k(x - y).................................(iii)
\end{array}\]
Now if we multiply equation (i) with x, equation (ii) with y and equation(iii) with z
We will get its as
\[\begin{array}{l}
x\log x = kx(y - z)\\
y\log y = ky(z - x)\\
z\log z = kz(x - y)
\end{array}\]
So now let us add all three of them and we will get it as
\[\begin{array}{l}
\therefore x\log x + y\log y + z\log z = kx(y - z) + ky(z - x) + kz(x - y)\\
\Rightarrow x\log x + y\log y + z\log z = k\left( {xy - xz + yz - xy + yz + xz - yz} \right)\\
\Rightarrow x\log x + y\log y + z\log z = k \times 0\\
\Rightarrow x\log x + y\log y + z\log z = 0
\end{array}\]
Now by using the property of log, \[x\log x = \log \left( {{x^x}} \right)\] we will get the whole thing as
\[ \Rightarrow \log \left( {{x^x}} \right) + \log \left( {{y^y}} \right) + \log \left( {{z^z}} \right) = 0\]
Now again we know that \[\log x + \log y + \log z = \log (xyz)\]
So by using this property of log we are getting
\[ \Rightarrow \log \left( {{x^x}.{y^y}.{z^z}} \right) = 0\]
Again if we take the log to the other side we will get it as
\[ \Rightarrow \left( {{x^x}.{y^y}.{z^z}} \right) = 1\]
Which is the correct answer and which means that option A is the correct option here.
Note: \[\log x = 0\] is \[x = 1\] because we know that logarithm in mathematics is treated as log base e so here \[{\log _e}x = 0\] is basically \[x = {e^0} = 1\] . In other words we can also say that the antilog of 0 is 1.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
Define least count of vernier callipers How do you class 11 physics CBSE
The combining capacity of an element is known as i class 11 chemistry CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Find the image of the point 38 about the line x+3y class 11 maths CBSE
Can anyone list 10 advantages and disadvantages of friction
Distinguish between Mitosis and Meiosis class 11 biology CBSE